Evaluation of the relationship between religious beliefs and academic achievements of dental students - Ramin Sarchami; Shakiba Rajaei; Shima Aalaei (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Considering the importance of the academic level of university graduates in the advancement of communities, it is necessary to evaluate factors affecting the academic achievements of university students. Therefore, this study investigated the relationship between religious beliefs and academic achievements of students in the Dental School in Qazvin University of Medical Sciences. MATERIALS AND METHODS: In this correlational study, all the dentistry students in the last 4 years of education were selected as the study samples. Of 109 students who had the inclusion criteria, 81 (31 males and 50 females) completed the questionnaires. The data collection tools were three questionnaires, including Gluck-Stark's questionnaire, two researcher-made questionnaires on "sympathy with and responsibility for patients," and the "self-satisfaction" questionnaire. Data were analyzed with descriptive and deductive statistics (t-test, Friedman test, and Pearson's correlation coefficient). RESULTS: According to the analyses, a significant and positive correlation was found between religiosity and students' overall mean grades (r = 0.27, P = 0.016) or "sympathy with and responsibility for patients" (r = 0.21, P = 0.05). No significant correlation was found between self-satisfaction and religious beliefs. CONCLUSION: Based on the results of the present study, the religious beliefs of the students were at a moderate level. On the other hand, this variable had a direct relationship with academic achievement and responsibility. Therefore, attention has to be paid to the promotion of these beliefs among students in colleges. Reinforcement of religious beliefs will improve the students' academic achievement. Based on the findings of this study, it should be considered by university professors and educational planners that the average score of students with higher religiosity was higher, and with the increase of religious beliefs, academic achievement is increased.